Efficacy and safety of sublingual immunotherapy for allergic rhinitis: A network meta-analysis - Ji, Zao; Jiang, Feifei (Frontiers in Immunology, 2023)
Background To systematically evaluate the clinical efficacy and safety of sublingual immunotherapy for allergic rhinitis (AR) and provide evidence for clinical treatment. Methods A literature search was performed on the China National Knowledge Infrastructure (CNKI), Wanfang database, PubMed, Web of Science, Cochrane Library, and Embase database. Data from randomized controlled trials (RCTs) of sublingual immunotherapy for AR were screened and extracted from the establishment of those databases to November 2022. Subsequently, a network meta-analysis was performed using a statistical software R 4.2. Results Totally 22 RCTs that met the inclusion and exclusion criteria and screened from 1164 literature were included. A total of 4941 AR patients were involved in the 22 trials, as well as 5 interventions including placebo, pharmacotherapy, subcutaneous immunotherapy_dust mite, sublingual immunotherapy_dust mite, and sublingual immunotherapy_ grass mix plus pollen extract. The results of network meta-analysis showed that, based on symptom scores after different interventions for AR, the most effective treatments for AR were in order as follows: sublingual immunotherapy_dust mite, subcutaneous immunotherapy_dust mite, sublingual immunotherapy_ grass mix plus pollen extract, placebo, and pharmacotherapy. Importantly, sublingual immunotherapy had fewer adverse reactions and higher safety. Conclusion Sublingual immunotherapy_dust mite for AR has the best efficacy, while traditional medicine has the worst. More high-quality studies with a large sample and multiple centers are needed to verify this conclusion in the future, so as to further provide more reliable evidence-based medical evidence for the clinical treatment options of AR patients.